Nietzsche’s impulse towards the development of a concept of God that transcends modern atheism and theism: a philosophical theological study - Buitendag, Johan (University of Pretoria, 2013)
Thesis (DD (Dogmatics and Christian Ethics))--University of Pretoria, 2005.